Ekspor-Impor Perikanan Indonesia Tahun 2025: Potensi, Daya Saing, Dan Tantangan Pasar Global - Nafasyah Kurnia Dewi (GLOBAL SCIENTS PUBLISHER, 2026)
This study discusses Indonesia’s fisheries export-import performance in 2025 by focusing on potential, competitiveness, and challenges in the global market. The fisheries sector has a strategic role in supporting national economic growth, generating foreign exchange, and strengthening Indonesia’s position as a maritime country. This article aims to analyze the performance of Indonesia’s fisheries exports, explain the role of fisheries imports, and examine trade balance conditions and competitiveness challenges in the international market. This research uses a qualitative descriptive method with a literature study approach. Data were obtained from official reports of the Ministry of Marine Affairs and Fisheries and relevant scientific articles discussing fisheries trade, export competitiveness, and global market dynamics. The results show that Indonesia’s fisheries exports in 2025 reached USD 6.27 billion, dominated by shrimp, tuna-skipjack, squid-cuttlefish-octopus, crab, and seaweed. Although imports still occur to meet industrial and consumption needs, Indonesia continues to record a fisheries trade surplus. Strengthening product quality, market diversification, value-added processing, and sustainability practices are needed to improve competitiveness in the global market..